Formation of NiCo2V2O8 yolk – double shell spheres with enhanced lithium storage properties - Lu, Yan (2020)
Complex nanostructures with multi‐components and intricate architectures hold great potential in developing high‐performance electrode materials for lithium‐ion batteries (LIBs). Herein, we demonstrate a facile self‐templating strategy for the synthesis of metal vanadate nanomaterials with complex chemical composition of NiCo2V2O8 and a unique yolk–double shell structure. Starting with the Ni‐Co glycerate spheres, NiCo2V2O8 yolk–double shell spheres are synthesized through an anion‐exchange reaction of Ni‐Co glycerate templates with VO3− ions, followed by an annealing treatment. By virtue of compositional and structural advantages, these NiCo2V2O8 yolk–double shell spheres manifest outstanding lithium storage properties when evaluated as anodes for LIBs. Impressively, an extra‐high reversible capacity of 1228 mAh g−1 can be retained after 500 cycles at a high current density of 1.0 Ag−1.